The Daughters of Hegel. From phallic statehood to the gender revolution - Rafael Arce (Estudios de Teoría Literaria, 2020)
Las hijas de Hegel by Osvaldo Lamborghini has been a text little read by literary criticism. Automatic writing, memories, intimate diary, and poetic prose: the critic has paid special attention to the mentioned style of the author. On the other hand, historical and political questions have been investigated, always linked to the conjuncture and the experience of authoritarianism in Argentina. The reference to Hegel has deserved little attention or superficial attention. In this paper, we propose to examine The Daughters of Hegel as a critical reflection about the political consequences of the philosophy of the Spirit and the historical evolution of the nations of Latin America. Lamborghini examines Argentine history as the cyclical erection of authoritarian phallic-state oppression. In this context, Peronism would have been the historical experience of the emergence of the masses. But this experience, whose icon is the figure of Eva Perón, is conceived linked to the desire and the cathexis of the social field. The transformation of man into woman, finally, embodies the deconstruction of state authority in a disintegration of sovereignty in which the mass never becomes a nation.